Answer:
The inverse of the function is
[tex]{ \underline{f {}^{ - 1}(x) = \sqrt{ \frac{x + 4}{2} } }}[/tex]
Step-by-step explanation:
let the inverse of f(x) be m:
[tex]m = {2x}^{2} - 4 [/tex]
take 4 to the left hand side ( changes sign to positive ):
[tex]m + 4 = {2x}^{2} \\ \frac{m + 4}{2} = {x}^{2} [/tex]
take a square root on all sides:
[tex] \sqrt{ \frac{m + 4}{2} } = \sqrt{ {x}^{2} } \\ \\ x = \sqrt{ \frac{m + 4}{2} } [/tex]
substitute x in place of m:
[tex] {f}^{ - 1} (x) = \sqrt{ \frac{x + 4}{2} } [/tex]